Characterization of perovskite LaFeO3 synthesized by microwave plasma method for photocatalytic applications - Orawan Wiranwetchayan (2018)
© 2018 Elsevier Ltd and Techna Group S.r.l. Perovskite LaFeO3 nanoparticles were successfully synthesized by microwave plasma method combined with high temperature calcination at 700–1000 °C. The influences of calcination temperature on morphology, crystalline structure, purity and the atomic compositions of samples were studied. The photocatalytic performance of LaFeO3 was evaluated though the photodegradation of Rhodamine B (RhB) under visible light. In this research, the orthorhombic LaFeO3 nanoparticles showed band gaps in the range of 2.15–2.30 eV. The particle size increased with increasing in the calcination temperature, leading to the decreasing in the surface area. The LaFeO3 sample calcined at 900 °C showed the highest photodegradation of 77.8% and the apparent rate constant of 0.0077 min−1 within 180 min because of the narrower of band gap and the higher crystalline degree and oxygen adsorption.